Jenis-Jenis Tikus (Rodentia: Muridae) dan Pakan Alaminya di Daerah Pertanian Sekitar Hutan di Kabupaten Banggai, Sulawesi Tengah - Bambang Agus Suripto; Aganto Seno; Sudarmaji Sudarmaji (Universitas Gadjah Mada, 2002)
The species diversity of rats (Fam. Muridae) differs on each island in Indonesia. There are at least 16 genera of 41 species of rats in Sulawesi Island. Recently it has been reported that rats attack relatively new paddy field surrounding forest, but the identity of the species is still unknown. The objectives of this research are to assess the rat’s diversity and the guilds of rats living around the forest. The research was done in agricultural area surrounding forest in Siuna, foothill of Tompotika Mt, Banggai Regency, Central Sulawesi. Rats in the forest and coconut plantation were captured using Shermann traps, which were randomly situated. Rats in paddy field were captured by trap barrier system (TBS). Habitat condition and the presence of predators were recorded. All rat specimens were identified to their scientific names using Corbert & Hill (1992). Their stomach contents was put in 70% alcohol, taken 5 samples for each stomach, and analyzed under a microscope to determine their feed. The data were interpreted descriptively, which was emphasizing its potency as a pest. The result shows that there are 7 genera i.e. Bunomys, Maxomys, Taeromys, Paruromys, Tateomys, Mus, Rattus and 18 species of rats. Bunomys sp., B. penitus, B. prolatus, Maxomys sp., M. musschenbroekii, M. dollmani, Taeromys sp., T. callitrichus, T. celebensis, T. rhinogradoide, Paruromys ursinus, P. camurus, and P. dominator occupy the forest. B. heinrichi, B. prolatus, M. musschenbroekii, P. camurus, Mus musculus; and Rattus nitidus ocupy coconut plantation. R. argentiventer, R. exulans and R. nitidus occupies the paddy field. The stomach content examination shows that B. prolatus, M. musschenbroekii, R. exulans, R. nitidus, and T. rhinogradoide eat mostly animal materials, especially member of Phylum Arthropoda; R. argentiventer mostly eat plant material, especially member of Family Graminae (grass family). Unfortunately the stomach contents B. heinrichi, B. penitus, M. musculus, and T. callitrichus couldn’t identified since it was either empty and or severely damaged. The field data and literature study, suggest that R. argentiventer and R. exulans are pests or at least potential pests in the paddy field. B. heinrichi, B. penitus, B. prolatus, M. musschenbroekii, M. musculus, R. nitidus, and T. callitrichus are potential pests, since those species are basically omnivorous. However M. musculus prefers to eat grains. Meanwhile T. rhinogradoides is not potential to be a pest since it is carnivorous.